Smoking Practices among Students (Study on Social Science’s Students of Surabaya State University) - Alfarizi, Izzulhaq; Agus Machfud Fauzi (Paradigma, 2025)
Abstract The development of modernization in the 21st century certainly has an impact on changes in people’s conditions, especially on their way of acting and behavior in carrying out social life. The practice of smoking which was previously dominated by men, since many dynamic human changes have made the practice of smoking currently mostly carried out by women. Especially among female students on campuses now. It is undeniable that most female students in several Indonesian campuses have practiced smoking. Things that encourage these female students to practice smoking can occur due to environmental factors or their natural characteristics that make them practice smoking. All of these smoking actions are of course based on how cigarettes are assessed and assumptions on the lives of female students. Because from some female students, cigarettes are an item that can vent their stress and anxiety in responding to problems in themselves. As for those who practice smoking, it is only based on following along with the trend of women smoking or it can be said as a lifestyle. Therefore, in this study the author has an interest in "Smoking Practices among female students" which takes a review of his analysis of female students of the Faculty of Social Sciences and Law, Surabaya State University. Keywords: Student, Change, Smoking, Practice, Action